CODE MIXING USED BY ENGLISH LITERATURE STUDENTS OF THE SEVENTH SEMESTERS IN DR.SOETOMO UNIVERSITY - Budianto, Suhartawan; Muhroji, Muhroji (Dinamika : Jurnal Sastra dan Budaya, 2016)
Study entitled "Code Mixing Used by English Literature Students of the Seventh Semester in Dr. Soetomo University" is a sosoiolinguistic study. The selection of objects is based on the environment of Indonesian and English bilingual languages in a circle of seventh semester English literature students at Universitas Dr. Soetomo. This thesis uses descriptive qualitative method. This study aims to determine the type of Code Mixing and the reasons of using code mixing by employing Hoffman's theory. Finally, it was revealed in the findings that the most dominant type of code mixing were Used by English Literature Students of the Seventh Semester In Dr. Soetomo University is Intra-Sentential Code-mixing in the form of phrases. Meanwhile, the dominant intra-lexical code mixing found is verb. As a whole, code mixing is found in the form of inserting English codes into Indonesian utterances. Involving changes to pronunciation only shows four data. This research also reveals the most dominant reasons for using code mixing among seventh semester students is to express group identity.Â Keywords: Sociolinguistic, Bilingual and Code-Mixing.